The genus Zygoneura Meigen in China, with descriptions of three new species (Diptera, Sciaridae)a - Zhang, Su-Jiong; Wu, Hong; Huang, Junhao (Zootaxa, 2010)
The taxonomy of the genus Zygoneura Meigen in China was studied. Seven species are recognized, including three new species that are described and illustrated: Zygoneura disparilis Zhang & Wu sp. nov., Z. longa Zhang & Wu sp. nov., and Z. occidens Zhang & Wu sp. nov. In addition, Z. sajanica Mamaev, 1976, and Z. sciarina Meigen, 1830 are reported for the first time from China. A key to the Palaearctic and Oriental regions species is also provided.